2022
DOI: 10.3389/fpls.2022.949752
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of parental ultraviolet-B environment shapes the growth strategies of clonal Glechoma longituba

Abstract: Although there is an increasing debate about ecological consequences of environmental predictability for plant phenotype and fitness, the effect of predictability of parental environments on the offspring is still indefinite. To clarify the role of environmental predictability in maternal effects and the growth strategy of clonal offspring, a greenhouse experiment was conducted with Glechoma longituba. The parental ramets were arranged in three ultraviolet-B (UV-B) conditions, representing two predictable envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Many studies focused on the same or different environments of clonal plant progeny and parents [ 6 , 7 ], However, clonal plants often face heterogeneous environments in natural environments, while it’s in heterogeneous environments usually tend to perform habitat selection [ 2 , 41 ]. Also, studies have shown that DNA methylation may be involved in the habitat selection behaviour of clonal plants [ 33 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focused on the same or different environments of clonal plant progeny and parents [ 6 , 7 ], However, clonal plants often face heterogeneous environments in natural environments, while it’s in heterogeneous environments usually tend to perform habitat selection [ 2 , 41 ]. Also, studies have shown that DNA methylation may be involved in the habitat selection behaviour of clonal plants [ 33 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parental environmental signals that can be perceived by clonal offspring via a connected spacer (stolon or rhizome) have been proven ( Liu et al., 2015 ; Guo et al., 2022 ; Tie et al., 2022 ; Xue et al., 2022 ). Moreover, in this study, although touch only took place between parents, its impact was transferred to their offspring, causing the decrease of ramet number, leaf area, leaf biomass and leaf investment (decreased LAR and LMR), but relatively less reduction in stolon biomass (increased S/L).…”
Section: Discussionmentioning
confidence: 99%
“…The maternal effect and the light adaptation of clonal offspring induced by it have been discussed in many studies. Some documented that the phenotype induced by the maternal effect may facilitate offspring to pre-adapt to a light environment ( Guo et al., 2022 ; Tie et al., 2022 ; Xue et al., 2022 ). The alternative view, however, stated that parental shading effects contributed little to the tolerance of clonal offspring to shading ( Dong et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the kernels, the most significant changes were a decrease in empty grain rate and an increase in thousandgrain weight. In a study on the clonal plant Glechoma longituba L., it was found that the progeny allocated more resources for defense and increased flavonoid and anthocyanin contents under unpredictable UV-B conditions [45]. Overall, after the stressor was removed, rice experienced negative effects due to stress memory, as the growth strategy was to inhibit growth, allocate more resources to defense and offspring reproduction, increase proanthocyanidin content, and produce fewer but larger seeds.…”
Section: Stress Memory Effect On Transgenerational Plasticitymentioning
confidence: 99%